Thinking in C++ - Eckel, Bruce (Prentice Hall, 2000)
Introduction to objects, inheritance, composition, polymorphism, exception handling, analysis and design fundamentals, advantages of C++, transitioning from C, compiling and building programs, writing C++ functions, flow control, C++ operators, data types, casting, debugging tips, pointers to functions, designing reusable C++ classes, conditional compilation and header files, access specifiers, constructors and destructors, function overloading and default arguments, using const and static effectively, inlining, namespaces, references, copy constructors, operator overloading, using new and delete for dynamic objects, virtual functions, abstract classes, introduction to templates, and iterators.